1999
DOI: 10.1001/archinte.159.7.670
|View full text |Cite
|
Sign up to set email alerts
|

Severe Paroxysmal Hypertension (Pseudopheochromocytoma)

Abstract: Severe, symptomatic paroxysmal hypertension always generates suspicion of a pheochromocytoma, a catecholamine-secreting tumor. However, most patients with this disorder do not have this tumor and their condition remains undiagnosed and ineffectively treated. This case series, summarizing the course of 21 such patients, suggests a cause and an effective treatment approach. All 21 patients insisted that the paroxysms were not related to stress or emotional distress, initially discouraging consideration of a link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(29 citation statements)
references
References 11 publications
0
28
0
1
Order By: Relevance
“…Characterization of each of these can be a matter of perspective and context (Herman, 2013). Stress responses promote survival by helping organisms meet the demands of a variety of acute challenges in the short-term (Huether, 1996; Levine and Ursin, 1991; McEwen, 2004; Ursin and Olff, 1993), yet they are also linked with impaired functioning and the development of pathology under repeated activation or extended conditions (Chrousos, 2000; Mann, 1999; McEwen, 2000; Pasternac and Talajic, 1991; Paykel, 1976; Shively et al, 2009; Vanitallie, 2002). One popular formulation of maladaptation is allostatic load, and refers to the cumulative effects or "costs" generated following repeated stress exposure on multiple physiologic systems (Brindley and Rolland, 1989; McEwen and Stellar, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Characterization of each of these can be a matter of perspective and context (Herman, 2013). Stress responses promote survival by helping organisms meet the demands of a variety of acute challenges in the short-term (Huether, 1996; Levine and Ursin, 1991; McEwen, 2004; Ursin and Olff, 1993), yet they are also linked with impaired functioning and the development of pathology under repeated activation or extended conditions (Chrousos, 2000; Mann, 1999; McEwen, 2000; Pasternac and Talajic, 1991; Paykel, 1976; Shively et al, 2009; Vanitallie, 2002). One popular formulation of maladaptation is allostatic load, and refers to the cumulative effects or "costs" generated following repeated stress exposure on multiple physiologic systems (Brindley and Rolland, 1989; McEwen and Stellar, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, hypertension episodes are usually sudden in onset and are often accompanied by physical symptoms including headaches, dizziness, nausea, diaphoresis, chest pain, and palpitations [ 2 ] which are indistinguishable from the symptoms observed in a patient with pheochromocytoma. Frequency of these episodes ranges from daily to less than one per month and the duration of the episodes may range from minutes to days [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Frequency of these episodes ranges from daily to less than one per month and the duration of the episodes may range from minutes to days [ 4 ]. In their series of 21 patients, Mann found that women are more often affected than men [ 2 ] and that the majority of patients had 1–3 attacks per week. The most frequent symptoms were chest pain (80%) followed by light-headedness (68%), headache (68%), nausea, and diaphoresis (62%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other causes of paroxysmal hypertension include labile hypertension, hyperthyroidism, renovascular hypertension, seizure disorder, migraine, alcohol withdrawal, drugs such as cocaine, amphetamines, or clozapine [2], carcinoid syndrome, panic disorder, and baroreflex failure [3]. In some cases of paroxysmal hypertension, no obvious cause could be identified, though it has been suggested that careful psychosocial interviewing may uncover repressed emotional distress that patients may not be aware of [4]. …”
Section: Discussionmentioning
confidence: 99%